Pendidikan Islam Sebagai Sebuah Sistem dalam Pendidikan di Indonesia - Nurmila, Nurmila; Silahuddin, Silahuddin (Indo-MathEdu Intellectuals Journal, 2024)
The Islamic education system aims to develop human nature (basic potential) in order to become human resources with noble character. The Islamic education system is based on the ideology of monotheism which is sourced from the Qur'an and Al-Sunnah as well as ijtihad. This study uses a literature review approach. Literature reviews focus on the analysis and synthesis of relevant academic sources. In this study, data and information that support writing are collected by searching the library, searching for relevant sources, and searching for data through the internet. The analysis is carried out through a systematic process in identifying, categorizing, and comparing various strategies and methods used in the Islamic education environment in Indonesia. The results of this study explain that the system in the context of education refers to the education system or learning system, which includes various elements, processes, and structures involved in the implementation of education. This system includes the ways in which education is delivered to students, the rules that govern educational activities, and the structure of the institution that organizes it. The Islamic education system in Indonesia has characteristics that have developed along with the long history of Islamic civilization in the country. Islamic education in Indonesia can be found in various forms, ranging from formal to informal educational institutions